Evaluation of phthalazinone phosphodiesterase inhibitors with improved activity and selectivity against Trypanosoma cruzi. (20th December 2019) - De Araújo, Julianna Siciliano; da Silva, Patrícia Bernardino; Batista, Marcos Meuser; Peres, Raiza Brandão; Cardoso-Santos, Camila; Kalejaiye, Titilola D; Munday, Jane C; De Heuvel, Erik; Sterk, Geert Jan; Augustyns, Koen; Salado, Irene G; Matheeussen, An; et al.
Abstract: Background: Chagas' disease, caused by the protozoan parasite Trypanosoma cruzi, needs urgent alternative therapeutic options as the treatments currently available display severe limitations, mainly related to efficacy and toxicity. Objectives: As phosphodiesterases (PDEs) have been claimed as novel targets against T. cruzi, our aim was to evaluate the biological aspects of 12 new phthalazinone PDE inhibitors against different T. cruzi strains and parasite forms relevant for human infection. Methods: In vitro trypanocidal activity of the inhibitors was assessed alone and in combination with benznidazole. Their effects on parasite ultrastructural and cAMP levels were determined. PDE mRNA levels from the different T. cruzi forms were measured by quantitative reverse transcription PCR. Results: Five TcrPDEs were found to be expressed in all parasite stages. Four compounds displayed strong effects against intracellular amastigotes. Against bloodstream trypomastigotes (BTs), three were at least as potent as benznidazole. In vitro combination therapy with one of the most active inhibitors on both parasite forms (NPD-040) plus benznidazole demonstrated a quite synergistic profile (xΣ FICI = 0.58) against intracellular amastigotes but no interaction (xΣ FICI = 1.27) when BTs were assayed. BTs treated with NPD-040 presented disrupted Golgi apparatus, a swollen flagellar pocket and signs of autophagy. cAMP measurements of untreated parasites showed that amastigotes have higher ability to efflux this second messenger than BTs. NPD-001 and NPD-040 increase the intracellular cAMP content in both BTs and amastigotes, which is also released into the extracellular milieu. Conclusions: The findings demonstrate the potential of PDE inhibitors as anti- T. cruzi drug candidates.